ANALISIS AGRIBISNIS UBI JALAR UNGU DI DESA TELADAN KECAMATAN CURUP SELATAN KABUPATEN REJANG LEBONG - Marlina, Yeni; Asriani, Putri Suci; Sumantri, Bambang (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
The aims of the research are to 1) determine factors that affect the production of ubi jalar ungu, 2) to know how much costs and revenues the ubi jalar ungu farming, 3) to determine the efficiency of the ubi jalar ungu farming, 4) to calculate how much added value from ubi jalar ungu processing into fried macaroni. This study sites was intentionally set in the village of Teladan. The data is obtained from the primary data and the secondary data, the respondents of ubi jalar ungu farmers was taken by census method. While the processor is home industry ZAHRA. The result shows that significant factos are seeds, Phonska fertilizers, manures and labors. While, land factor is not significant. The total cost for the ubi jalar ungu farming is Rp 2.900.054,13/Ut/Mt or Rp 8.209.106,83/Ha/Mt, and a revenue is Rp 3.241.570,87/Ut/Mt, or Rp 9.190.226,51/Ut/Ha. Result of the R/C ratio is 2,12, and the value is greater than one. It means that the farming is efficient. The added value of ZAHRA home industry is Rp 41.072,-/kg, with a profit of Rp 37.472,-/kg, and the rate of profit reaches 91.23 %. This benefit is a net plus, because it has been reduced by the share of the labor.